A Prayer for Democracy: Secretarian Violence and Regime Type in Indonesia - Donald Greenlees (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2021)
Indonesia has a long history of conflict with roots in ethnic, religious, communal and political difference. This was the inevitable consequence of unresolved tensions when the Republic of Indonesia was born in 1945. While a variety of differences over the nature of the state have emerged over the past 76 years, none have been more protracted or resistant to solution than those over religion. In a country where Islam commands the adherence of 87 percent of the population, but five other religions are officially recognized, it is not surprising that these divides should persist.